Elimination of transformer inrush currents by controlled switching. II. Application and performance considerations. - Brunke, J.H.
For pt. I see ibid., vol.16, no.2, p.276-80 (2001). Transformer inrush currents are high-magnitude, harmonic-rich currents generated when transformer cores are driven into saturation during energization. These currents have undesirable effects, including potential damage or loss-of-life to the transformer, protective relay misoperation, and reduced power quality on the system. Controlled transformer switching can potentially eliminate these transients if residual core and core flux transients are taken into account in the closing algorithm. This paper explores the practical considerations of core flux transients, performance of control strategies, and the application of circuit breakers to control transformer inrush transients
Keywords: Circuit breakers; Closing algorithm; Control strategies performance; Controlled switching; Core flux transients; Energization; Harmonic-rich currents; High-magnitude currents; Potential damage; Protective relay misoperation; Reduced power quality; Residual core; Residual flux; Transformer inrush currents elimination; Transformer inrush transients control; Transformer loss-of-life.; Transients elimination